Atomistic level aqueous dissolution dynamics of NASICON-Type Li1+xAlxTi2−x(PO4)3 (LATP). Issue 7 (3rd February 2022) - Sengul, Mert Y.; Ndayishimiye, Arnaud; Lee, Wonho; Seo, Joo-Hwan; Fan, Zhongming; Shin, Yun Kyung; Gomez, Enrique D.; Randall, Clive A.; van Duin, Adri C. T.
Abstract : The surface dissolution at the LATP aqueous interface is a sequentially dynamic process starting with phosphate dissolution destabilizing the NASICON structure and continues with a titanium-rich secondary phase formation. Abstract : Advancing the atomistic level understanding of aqueous dissolution of multicomponent materials is essential. We combined ReaxFF and experiments to investigate the dissolution at the Li1+ x Al x Ti2− x (PO4 )3 -water interface. We demonstrate that surface dissolution is a sequentially dynamic process. The phosphate dissolution destabilizes the NASICON structure, which triggers a titanium-rich secondary phase formation.